Potensi implementasi Education for Sustainable Development (ESD) dalam pembelajaran IPA di MTs Nahdlatul Ulama Mranggen Kabupaten Demak - Sri Rahmawati; Fenny Roshayanti; Ary Susatyo Nugroho; Muhammad Saipul Hayat (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to determine the potential for the implementation of Education for Sustainable Development (ESD) in science learning for students at MTs Nahdlatul Ulama Mranggen, Demak Regency. The research used a qualitative descriptive method. Data collection techniques by interview, observation, and documentation. The data obtained were then analyzed using the Miles and Huberman analysis model for further conclusions to be obtained. The results showed the potential of ESD implemented in science learning at MTs Nahdlatul Ulama Mranggen. The data is seen through: (a) teachers' understanding of ESD, (b) integrating the values ??of ESD perspectives in KI and KD in Science subjects by analyzing KI and KD for Science Learning in class VII, and (c) potential implementation of ESD which allows it to be implemented in MTs Nahdlatul Ulama Mranggen. The results of the integration of data on aspects of integration in the three perspectives of Education for Sustainable Development (ESD) KI and KD class VII in science learning show that the values ??of ESD (socio-cultural, environmental and economic perspectives) have the potential to be applied in science learning at MTs Nahdlatul Ulama Mranggen Demak Regency.